Risk Management in Moroccan Healthcare Organizations: An Overview - et. al., En-Naaoui (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The institute of medicine asserts that to err is human: building a safer health system (Linda T et al, 2000). For this reason risk management takes an important place in healthcare decision-making process within the objective of ensuring the management of emergencies, which cannot always be anticipated in advance, but will cause serious consequences if they occur (Li Guo, 2015). In fact, risk management is defined as a set of activities and processes of identification, analysis, evaluation, treatment, reducing, communication and monitoring potential failures and adverse events in purpose to provide a better quality of service and a system able to insure protection of patients, workers, equipment, stakeholders and the environment. Thus, this paper aims to present a structured review of publications that highlight risk management topic in healthcare sector by proposing new approaches, applying existed techniques or implementing risk assessment plans in Moroccan healthcare organizations especially Moroccan hospitals.